A minority of proliferating human CD4+ T cells in antigen-driven proliferation assays are antigen specific - Bhattacharjee, Pushpak; Pakusch, Miha; Lacorcia, Matthew; Chiu, Chris Y.; Liu, Xin; Tresoldi, Eleonora; Foster, Abby; King, Laura; Cameron, Fergus J.; Mannering, Stuart I. (Frontiers in Immunology, 2024)
Antigen-driven T-cell proliferation is often measured using fluorescent dye dilution assays, such as the CFSE-Based Proliferation Assay. Dye dilution assays have been powerful tools to detect human CD4+ T-cell responses, particularly against autoantigens. However, it is not known how many cells within the proliferating population are specific for the stimulating antigen. Here we determined the frequency of CD4+ T cells specific for the stimulating antigen within the antigen responsive population of CFSE-based proliferation assays. We compared CD4+ T cell responses to a type 1 diabetes autoantigen, (proinsulin C-peptide) and to a vaccine antigen (tetanus toxoid). The TCRs expressed by antigen-responsive CD4+ T cells were sequenced and their antigen specificity was tested functionally by expressing them in a reporter T-cell line. Responses to C-peptide were weak, but detectable, in PBMC from individuals with T1D; whereas responses to tetanus toxoid were much stronger. The frequency of antigen specific CD4+ T cells correlated with the strength of the response to antigen in the proliferation assay. However, antigen specific CD4+ T cells were rare amongst antigen-responsive CD4+ T cells. For C-peptide, an average frequency of 7.5% (1-11%, n=4) of antigen-responsive CD4+ T cells were confirmed to be antigen specific. In the tetanus toxoid stimulated cultures on average of 45% (16-78 %, n=5) of the antigen-responsive CD4+ T cells were tetanus toxoid specific. These data show that antigen specific CD4+ T cells are a minority of the cells that proliferate in response to antigen and have important implications for in vitro CD4+ T-cell proliferation assays.